Corpus, máquinas e afetos: as experiências homossexuais na contemporaneidade - Colpani, Felipe Pancheri (Universidade Federal de São Carlos, 2015)
This research aims to analyze the production of homosexual experiences in contemporary times, with the investigative territory, social network Facebook. The space network connections [cyberspace] have been constituted as new production space morphologies for homosexuals. The technoculture’s virtual machines present themselves as social spaces of projection, memory and new developments. Emerged in a trans-discursive network connections, homosexuals can assume ownership of virtual machines to the ongoing reconstruction of its virtuality, understood as a mobile incorporeal flow that is transmuted in connection with each other. The social network Facebook is configured as a network of connections equipped by axes and directions, allowing individuals movements of deterritorial and intensive meetings, under a spatial mosaic hybrid, circumscribed in a multitude of territories and ciber-regions spread across the Global Village Machinic. The deterritorialized open cyberspace, solidifies as a space recorded by a heterogeneity of spatial elements, allowing the passage of flows and practices, and provide new experiences, which can move with the hetero-capitalism power centers. The analysis is centered on the materialistic production os [cyber]space, which allowed the outline of contemporary social production, combined with discursive production, through what is stated and registered on Facebook. A symbiosis that allowed me machining of existential production scenario in which these homosexuals are territorialized. The collection of discursive practices occurred from a virtual ethnography in the most closed group of homosexuals in Brazil, a nomadic territory of bodies and utterances that connects all to a central point: the uniqueness of homosexual desire. A creation of space for new experiences and affectivity, as well as a virtual closet. In this group, there are forces of coalescence: transgression forces and forces that capture the heterocapitalismo standard, constituting as an inductor territory of processes and connections that may even break with the reactionary encodings of global simulations of the Patriarchal-Heteroapitalist Empire. Through the analysis of the discursive production of homosexuals on Facebook, notes that homosexual experiences of today is based on a constant exchange between real and virtual, online and offline, corpus and machines under a profusion of new experiences and new performativities, passing by a social production of connections fight and claims and new groupings by affection.
Global village machinic: homosexual experiences; hetero-capitalism
Keywords: Homossexualidade; Homosexuality; Facebook (Rede social on-line); Facebook (Electronic resource); Ciberespaço; Cyberspace; Aldeia Maquínica Global; Global Village Machinic; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO